If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -96 = 4u + -10 + -27u + -6 Reorder the terms: -96 = -10 + -6 + 4u + -27u Combine like terms: -10 + -6 = -16 -96 = -16 + 4u + -27u Combine like terms: 4u + -27u = -23u -96 = -16 + -23u Solving -96 = -16 + -23u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '23u' to each side of the equation. -96 + 23u = -16 + -23u + 23u Combine like terms: -23u + 23u = 0 -96 + 23u = -16 + 0 -96 + 23u = -16 Add '96' to each side of the equation. -96 + 96 + 23u = -16 + 96 Combine like terms: -96 + 96 = 0 0 + 23u = -16 + 96 23u = -16 + 96 Combine like terms: -16 + 96 = 80 23u = 80 Divide each side by '23'. u = 3.47826087 Simplifying u = 3.47826087
| 5+5x=11+7x | | 123=60w | | 3L+3(L-5)= | | 5m+7=13+5m | | 4+6*-4=8*-4 | | 89=20h | | x^2+13x-26=0 | | 10+8x=6x+4x | | 4+6x-4=8x-4 | | -5ac^5(4c^6+9a^2-2)= | | d[m]=5m+320 | | a^3+a^2-a-1=0 | | 4+6z=8z | | 82.5=5.5r | | 6z+4=8z | | 2b+5b=7b | | 294=56x+49-3x+9 | | f[n]=n-1 | | f[n]=[n-1][n-2] | | 4s+3=7s | | f[n]=n+2n+5 | | 42x+-4= | | x-3+6x=-10 | | 4+3(4n+3)-n= | | 5k-1/2=3/2 | | 6s-2=8s | | 5(x-8)=3(3x-40) | | 4+3(4n+6)-n= | | 9x-6(x-1)=1 | | 6(d-6)=4(d-60)+2d | | -7x+(-7x-30)=36 | | 9mn/4n |